Pengaruh Lingkungan Sekolah dan Efikasi Diri terhadap Hasil Belajar Siswa Mata Pelajaran Ekonomi SMA Negeri 1 Tambang - Anggraini, Ega; Hendripides; Rizka, Mifta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of the school environment and self-efficacy on student learning outcomes in economics at SMA Negeri 1 Tambang. The problem addressed is the low student learning outcomes, which are suspected to be caused by a lack of support for the school environment and self-efficacy. The methodology used was a quantitative descriptive approach, with a population of 165 students and a sample of 63 students drawn using proportional random sampling. Data were collected through questionnaires to measure the school environment and self-efficacy, as well as documentation of final semester exam scores for learning outcomes. Data analysis was performed using multiple linear regression to test the effect of the independent variables on the dependent variable. The results showed that the school environment and self-efficacy significantly influenced student learning outcomes, with a coefficient of determination (R2) of 59.1%. A t-test indicated that the school environment and self-efficacy each significantly influenced learning outcomes with significance values ​​of 0.001 and 0.000, respectively. These findings emphasize the importance of developing the school environment and self-efficacy in improving student learning outcomes.